Advancements in antibiofouling hydrogel-based approaches for the removal of short-chain per- and polyfluoroalkyl substances in drinking water treatment - Donovan, Kyana K-A.; Fermin, Genesis T.; Vigil, Iliana; Shaker, Sundus; Paulino, Richerly A.; Difo, Robin; Ye, Yuemei (Frontiers in Chemical Engineering, 2025)
Per- and polyfluoroalkyl substances (PFAS) are emerging contaminants with increasing health concern due to their persistence, widespread presence, and adverse health effects. Short-chain PFAS, in particular, are more challenging to remove using conventional water treatment technologies. Hydrogel adsorbents have shown as a promising solution for short-chain PFAS removal, offering high adsorption capacity, rapid kinetics, and tunable material properties. However, biofouling contamination which is easier to happen on wet hydrogels adsorbents compared with conventional adsorbents in water treatment process, could significantly reduce adsorption efficiency, shorten operational lifespan, and increase overall costs. Antibiofouling modifications present a viable strategy to enhance hydrogel functionality in drinking water treatment applications. This review summarizes recent advancements of hydrogel in antibiofouling and short-chain PFAS removal applications through functional group modifications. Furthermore, it highlights gaps in the current literature, particularly the lack of studies on the development and evaluation of hydrogels with both biofouling resistance and short-chain PFAS removal capabilities for drinking water treatment applications.